Pengaruh Service Excellent, Keamanan, Dan Kecepatan Pelayanan Terhadap Keputusan Nasabah Muslim Menggunakan Jasa Pegadaian CP Kartasura - Lestari , Nuri; Widyaningsih, Meilana (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to determine and analyze Excellent Service, Security, and Speed ​​of Service on Muslim Customers' Decisions to Use Pegadaian CP Kartasura services. This research uses a quantitative approach method using the SPSS 25 application by distributing questionnaires during the research period. This research uses the population of Pegadaian CP Kartasura customers by taking a sample of 120 customers who are Muslim. The research methods used are Instrument Test, Classical Assumption Test, Multiple Linear Regression Test, Model Determination Test, and Hypothesis Test. The research results show that Service Excellent has a positive and significant effect on the decision of Muslim customers to use CP Kartasura pawnshop services, Security has a positive and significant effect on the decision of Muslim customers to use CP Kartasura pawnshop services, and Service Speed ​​has a positive and significant effect on the decision of Muslim customers to use CP pawnshop services. Kartasura.